(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
Engineered nanomaterials have increased for their positive impact in improving many sectors of economy including agriculture. Silver nanoparticles (AgNPs) have been implicated nowadays to enhance seed germination, plant growth, improvement of photosynthetic quantum efficiency and as antimicrobial agents to manage plant diseases. In this study, we examined effect of AgNPs dosage on seed germination of three plant species; corn (Zea mays L.), watermelon (Citrullus lanatus (Thunb.) Matsum. & Nakai) and zucchini (Cucurbita pepo L.). Therefore, this experiment designed to study the effect of AgNPs on germination percentage, germination rate, mean germination time, root length, fresh and dry weight of seedling for the three spices. Seven concentrations (0.05, 0.1, 0.5, 1, 1.5, 2 and 2.5 mg/L) of AgNPs were examined at seed germination stage. The results showed that the three spices revealed different dosage response to AgNPs on germination percentage and the measured growth characters. Germination rate values were enhanced for the three plants in response to AgNPs. Significant enhancement in germination percentage values for watermelon and zucchini plants were observed by treatment with AgNPs in comparison with nontreated seeds. AgNPs showed toxic effect on corn roots elongation whereas watermelon and zucchini seedling growth were positively affected by certain concentration of AgNPs. This study showed that exposure to AgNPs caused both positive and negative effects on plant growth and germination.